TWENTY YEARS TRENDS OF OBESITY AND ARTERIAL HYPERTENSION AND THEIR ASSOCIATION IN RUSSIA - S. A. Shalnova; A. D. Deev; Yu. A. Balanova; A. V. Kapustina; A. E. Imaeva; G. A. Muromtseva; N. V. Kiseleva; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2017)
The prevalence of obesity and obesity-related disorders has been increasing in the world during last decades, reaching the level of epidemics, being one of the key challenge for medical society and healthcare systems in developed countries.Aim. To evaluate the trends of arterial hypertension (AH) and obesity in Russia for the last 20 years.Material and methods. Into analysis, the results form 3 studies included, by identical protocol, performed in 1993, 2003, 2013 with participation of the National Research Center for Preventive Medicine. The data of general investigation was analyzed, of 55640 men and women at the age 25-64 y.o. In the analysis, the social and demographic data was included, AH, body mass index, smoking, alcohol consumption, heart rate.Results. The prevalence of AH in men in 1993 was 43,0%, declining by 2003 to 36,9%, and significantly increased in 2013 (47,3%). From 2003 to 2013 the prevalence of AH increased by approx. 20%, and of obesity — raised two times during the period. In females, contrary, AH prevalence decreased from 1993 to 2013; and if during 1993-2003 gradient was 15,4%, in 2003-2013 only 6,3%. If in 1993 the prevalence of AH predominated in females, in 2013 — in males. The relation of obesity and AH was assessed for every year of observation, by gender, in multiple regression model. It was found that, if corrected by age, educational level, smoking, alcohol consumption, and increased heartrate, chance of AH increases with obesity rate increase in both genders, 4,5-18 times. In men as in women the weakest relation of AH and obesity was found in 1993.Conclusion. Taken recent tendencies, it is important to develop strategies of prevention and management of obesity and AH, with the aim to decrease obesity-related AH development rate.